2021
DOI: 10.1016/j.ijcha.2021.100881
|View full text |Cite
|
Sign up to set email alerts
|

Remote magnetic navigation shows superior long-term outcomes in pediatric atrioventricular (nodal) tachycardia ablation compared to manual radiofrequency and cryoablation

Abstract: Background Catheter ablation (CA) is the first-choice treatment for tachyarrhythmia in children. Currently available CA techniques differ in mechanism of catheter navigation and energy sources. There are no large studies comparing long-term outcomes between available CA techniques in a pediatric population with atrioventricular reentry tachycardia (AVRT) or atrioventricular nodal reentry tachycardia (AVNRT) mechanisms. Objective This study aimed to compare procedural an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Consequently, our final analysis included 27 studies 7–9,16–39 (7 randomized studies and 20 observational studies analyzing 5110 patients who have AVNRT indicated for ablation. Cryoablations were performed 25 studies which categorized into 10 studies with 4‐mm tip catheter, 12 studies with 6‐mm tip catheter, and 3 studies with 8‐mm tip catheter.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, our final analysis included 27 studies 7–9,16–39 (7 randomized studies and 20 observational studies analyzing 5110 patients who have AVNRT indicated for ablation. Cryoablations were performed 25 studies which categorized into 10 studies with 4‐mm tip catheter, 12 studies with 6‐mm tip catheter, and 3 studies with 8‐mm tip catheter.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 27 studies 7–9,16–39 with retrievable information were considered for analysis. We conducted a descriptive assessment to evaluate the acute procedural success rate for each technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations